Determination of Operational Costs of PT. Antam Tbk. West Kalimantan Bauxite Mining Business Unit: Types of Letter of Credit (LC), Terms of Letter of Credit (LC), and Transaction Efficiency - Fajar Herdiaman, Indra; Ali, Hapzi (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This article conducts a study related to the Determination of Operational Costs of PT. Antam Tbk. West Kalimantan Bauxite Mining Business Unit: Types of Letter of Credit, Terms of Letter of Credit, and Transaction Efficiency. The research objects were obtained through online literature reviews such as Google Scholar, Semantic Scholar, and other academic online media as research objects. The main objective of this study is to formulate hypotheses regarding the influence of these variables for future research. The research method uses Systematic Literature Review and Library Search with the utilization of Artificial Intelligence (AI) to obtain related research, sourced from open access journals and e-books. The results of this study are: 1) Types of Letter of Credit affect Operational Costs; 2) Terms of Letter of Credit affect Operational Costs; and 3) Transaction Efficiency affects Operational Costs.